Exploring strategies to enhance democratic management practices in teacher education classrooms in a selected South African university - Omodan, Taiwo Christianah (University of the Free State, 2024)
Democratic classroom management practices play a vital role in fostering student participation and exposing learners to diverse perspectives and engagement opportunities in educational settings. However, there exists a significant disparity between the ideals of democratic education and the prevailing traditional classroom management approaches observed in university classrooms. In South Africa, the translation of democratic principles into actionable classroom management strategies remains a challenge, particularly within university classrooms. To address these challenges, this study examined the perceptions of student-teachers and lecturers regarding democratic classroom management practices in university-based teacher training. The study adopts critical theory as its guiding framework and employs a transformative research paradigm within a qualitative research approach. A participatory research design is utilised, with data being collected through observation and semi-structured interviews involving 10 student-teachers and 5 lecturers from a selected university in the Eastern Cape province of South Africa. Thematic analysis is employed to analyse the data. The study is divided into three publishable articles, with the main findings emphasising the necessity for comprehensive reforms in teacher education to establish inclusive and democratic learning environments that strike a balance between student autonomy and classroom discipline. Additionally, the study reveals resistance to participatory learning due to traditional teaching methods and institutional constraints, highlighting the need for systemic changes to promote equitable and inclusive democratic management practices in university classrooms. Finally, by emphasising student engagement, collaborative teaching, and critical reflection, the study underscores the importance of inclusive and democratic classroom environments in preparing students for real-world challenges. The study formulates and recommends a Democratic Classroom Management Model to facilitate effective democratic classroom management practices.

Demokratiese klaskamerbestuurspraktyke speel ’n deurslaggewende rol in die bevordering van studentedeelname en die blootstelling van leerders aan diverse perspektiewe en geleenthede tot betrokkenheid binne opvoedkundige omgewings. Daar bestaan egter ’n beduidende gaping tussen die ideale van demokratiese onderwys en die heersende tradisionele klaskamerbestuursbenaderings wat in universiteitsklaskamers waargeneem word. In Suid-Afrika bly die oordrag van demokratiese beginsels na toepasbare klaskamerbestuursstrategieë ’n uitdaging, veral binne universiteitsklaskamers. Om dié uitdagings aan te spreek, het hierdie studie die persepsies van onderwysstudente en dosente ondersoek rakende demokratiese klaskamerbestuurspraktyke binne universiteitsgebaseerde onderwysersopleiding. Die studie volg kritiese teorie as die teoretiese raamwerk en maak gebruik van ’n transformerende navorsingsparadigma binne ’n kwalitatiewe navorsingsbenadering. ’n Deelnemende navorsingsontwerp is gebruik, met data-insameling deur middel van waarneming en semigestruktureerde onderhoude met 10 onderwysstudente en 5 dosente aan ’n geselekteerde universiteit in die Oos-Kaap Provinsie van Suid-Afrika. Tematiese analise is gebruik om die data te ontleed. Die studie is gestruktureer in drie publiseerbare artikels, waarvan die hoofbevindinge die noodsaaklikheid beklemtoon van omvattende hervormings in onderwysersopleiding om inklusiewe en demokratiese leeromgewings te vestig wat ’n balans handhaaf tussen studente-outonomie en klaskamerdissipline. Daarbenewens toon die studie dat daar weerstand teen deelnemende leer bestaan weens tradisionele onderrigmetodes en institusionele beperkings, wat die behoefte aan sistemiese veranderinge om billike en inklusiewe demokratiese bestuurspraktyke in universiteitsklaskamers te bevorder, uitlig. Ten slotte, deur klem te lê op studentebetrokkenheid, samewerkende onderrig en kritiese refleksie, onderstreep die studie die belangrikheid van inklusiewe en demokratiese klaskameromgewings ter voorbereiding van studente vir werklike uitdagings. Die studie formuleer en beveel ’n Demokratiese Klaskamerbestuursmodel aan om effektiewe demokratiese klaskamerbestuurspraktyke te fasiliteer.

Diketso tsa bolaodi ba kopanelo ka hara phaposi ya borutelo bo molemo haholo ho etsa hore baithuti ba be le seabo esita le ho tsebisa baithuti ho mahlakore a fapaneng a tsebo le ho ba le menyetla dibakeng tsa thuto. Leha ho le jwalo, ho na le phapano e kgolo pakeng tsa mehopolo ya thuto ya kopanelo le thuto e ntseng e sebediswa e tlwaelehileng ya bolaodi ka hara phaposi ya boithatelo jwalokaha bo bonwa diphaposing tsa borutelo tsa yunivesithi. Mona Afrika Borwa, tsa maano a demokrasi ho ba mekgwa e ka phethahatswang e dula e le phephetso e kgolo, haholoholo ka hara diphaposi tsa yunivesithi. Ho fihlella diphephetso tsena, diphuputso tsena di hlahlobile kutlwisiso ya bomaithutwane ba matitjhere esita le barupelli mabapi le diketso tsa bolaodi ba kopanelo ka hara phaposi ya borutelo kwetlisong ya matitjhere e etswang yunivesithing. Diphephetso tsena di sebedisa lewa la ho phenyekolla e le moralo wa tsona wa tataiso mme di sebedisa hape diphuputso tsa diphetolo ka hara katamelo ya diphuputso tsa patlisiso ya boleng. Diphuputso tsa ho ba le seabo tsa ho ba le seabo di sebedisitswe mme dintlha tsa mme dintlha tsa diphuputso diphuputso di bokeleditswe ka ho tadima le ho ba le dipuisano tse kenyeletsang bomaithutwane ba matitjhere ba 10 le barupelli ba 5 ba tswang yunivesithing e kgethilweng ya provense ya Kapa Botjhabela mona Afrika Borwa. Tshekatsheko ya meelelo e sebedisitswe ho sekaseka datha kapa dintlha tsa diphuputso. Diphuputso tsena di arotswe diatikele tse tharo tse ka phatlalatswang, mme diphihlello tse kgolo di toboketsa bohlokwa ba tlhabollo ya thuto ya matitjhere ho theha ditikoloho tse kenyeletsang bohle le ditikoloho tsa thuto ka kopanelo tse tlisang botsitso pakeng tsa boikemelo ba baithuti le tataiso ka hara phaposi ya borutelo. Ho feta mona, diphuputso tsena di senola ho thibela ho ithuta ka ho ba le seabo ho ya ka mekgwa ya ho ruta ya kgale le dithibelo tsa institjushene, ho pepesa tlhokeho ya diphetoho tsa tshebetso e le ho ntshetsa pele diketso tsa bolaodi ba kopanelo ho tlisang tekatekano le ho kenyeletsa bohle ka hara diphaposi tsa borutelo yunivesithing. Qetellong, ka ho toboketsa kenyeletso ya baithuti, ho ruta ka kopanelo, le ho phenyekolla tsebo, diphuputso tsena di matlafatsa bohlokwa ba ditikoloho tsa kenyeletso ya bohle le phaposi ya borutelo tikolohong e lokisetsang baithuti bakeng sa diphephetso tsa lefatshe la nnete. Diphephetso tsena di theha le ho kgothaletsa Mokgwa wa Bolaodi ba Kopanelo ka hara Phaposi ya Borutelo e le ho potlakisa le ho nnetefatsa diketso tsa bolaodi ba kopanelo ba phaposi ya borutelo.

Izinqubo zokwengamela iklasi ngentando yeningi zibamba iqhaza elibalulekile ukuqguqguzela ukuhlanganyela kwabafundi futhi ukuvezela abafundi imiqondo eyehlukene kanye namathuba okuzibandakanya ezimeni zezemfundo. Yize noma kunjalo, kukhona ukungefani okukhulu phakathi kwemibono yemfundo yentando yeningi kanye nezindlela zokwenganyelwa kweklasi kwendabuko okuvamile okubonakala emaklasini asenyuvesi. ENingizimu Afrikha, ukuhumushela izimiso ezisebenzisekayo zentando yeningi emaswini okwengamela iklasi kuseyingqinamba, kakhulukazi emaklasini asenyuvesi. Ukubhekana nalezi zingqinamba, lolu cwaningo luhlole ukuqonda kwabafundi nothisha kanye nabafundisi basenyuvesi mayelana nezinqubo zokwenganyelwa kweklasi ngentando yeningi oqeqeshweni lothisha olwencike enyuvesi. Ucwaningo lusebenzisa injulalwazi ehlaziyayo njengohlaka olukhomba indlela futhi lusebenzisa ipharadayimu yocwaningo oluguqulayo endleleni yocwaningo yekhwalithethivu. Uhlelo locwaningo lokuzibandakanya luyasetshenziswa, nemininingo eqoqwe ngokubukela kanye nezingxoxo ezisakuhleleka okubandakanya abafundi nothisha abayi-10 kanye nabafundisi basenyuvesi aba-5 abaphuma enyuvesi esesifundazweni saseMpumakoloni eNingizimu Afrikha. Ukuhlaziya ngezindikima kwasetshenziswa ukuhlaziya imininingo. Ucwaningo lwehlukaniswe ngama-athikile amathathu akulungele ukusatshalaliswa, nemiphumela eqavile egcizelela isidingo sezinguquko ezibandakanya konke ekuqeqeshweni kothisha ukwakha izimo ezibandakanya konke futhi zokufunda ngentando yeningi. Okunye futhi, ucwaningo luveza ukumelana nokufunda ngokuzibandakanya ngenxa yezindlela zokufunda zendabuko kanye nezithiyo zezikhungo, okugqamisa isidingo sezinguquko ezihlelekile ukuqgugquzela ukulingana kanye nezinqubo zokwengamela ngentando yeningi ezibandakanya konke. Okokugcina, ngokugcizelela ukwenganyelwa kwabafundi, ukufundisa ngokubambisana, kanye nokuningi okuhlaziyayo, ucwaningo lugcizelela ukubaluleka kwezimo zokubandakanya konke kanye namaklasi entando yeningi ukulungiselela abafundi izingqinamba zomhlaba wangempela. Ucwaningo lwakha futhi luphakamisa iModeli Yokwengamela Amaklasi Entando Yeningi ukugquguzela izinqubo ezinempumelelo zokwenganyelwa kwamaklasi ngentando yeningi.
’n Ondersoek na strategieë om demokratiese bestuurspraktyke in onderwysklaskamers aan ’n geselekteerde Suid-Afrikaanse universiteit te bevorder
Ho hlahloba mekgwa ya ho ntshetsa pele diketso tsa bolaodi ba kopanelo ka hara diphaposi tsa borutelo tsa thuto ya matitjhere ho yunivesithi e kgethilweng ya Afrika Borwa
Thesis (Ph.D.(Education Management and Leadership))--University of the Free State, 2024
Keywords: Democratic practices; Classroom management; Democratic management practices; Teacher education; Demokratiese praktyke; Klaskamerbestuur; Demokratiese bestuurspraktyke; Onderwysersopleiding; Diketso tsa kopanelo; Bolaodi phaposing ya borutelo; Diketso tsa bolaodi ba kopanelo; Thuto ya matitjhere; Izinqubo zentando yeningi; ukwengamela iklasi; izinqubo zokwengamela ngentando yeningi; imfundo yothisha